2000
DOI: 10.1076/0271-3683(200008)2121-vft608
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase activity is enhanced during corneal wound repair in high glucose condition

Abstract: MMP activity was enhanced in healing corneal epithelium, both in in vitro and in vivo diabetic models, suggesting its involvement in diabetic keratopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…The glucose concentration, we used in the present study, is extremely higher than that in vivo situation, and it seems to be a little higher than those in some other in vitro experiments. However, in the experiments of SV-40 transformed HCEC, McDermott et al 4 and Takahashi et al 5 used 38 mM and 31.2 mM glucose as a high glucose, respectively. Therefore, we selected 36 mM glucose as a high glucose in the present experiments.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The glucose concentration, we used in the present study, is extremely higher than that in vivo situation, and it seems to be a little higher than those in some other in vitro experiments. However, in the experiments of SV-40 transformed HCEC, McDermott et al 4 and Takahashi et al 5 used 38 mM and 31.2 mM glucose as a high glucose, respectively. Therefore, we selected 36 mM glucose as a high glucose in the present experiments.…”
Section: Discussionmentioning
confidence: 98%
“…Due to the increasing numbers of diabetic patients and intraocular surgery, the pathogenesis and treatment of diabetic keratopathy has attracted a lot of attention. [4][5][6][7][8] Corneal epithelial wound healing is considered to be a highly organized series of events in which the cells initially adhere to the substrate, migrate, proliferate, and cover the wounded area. 9,10 Disturbance at any phase of the above process could delay corneal epithelial wound healing in diabetic keratopathy.…”
Section: Introductionmentioning
confidence: 99%
“…As diabetic corneas have slow and incomplete epithelial wound healing, and BM fragility and fragmentation, it is possible that proteinases are involved in these alterations. In fact, corneal epithelial cells in high glucose and rat diabetic corneal epithelium showed enhanced MMP activity during wound healing (Takahashi et al, 2000). Using gene microarrays, immunostaining, and zymography, our group has shown that ex vivo human diabetic corneas upregulated the expression of MMP-10 in the epithelium and keratocytes, MMP-3 in the keratocytes, and cathepsin F in the epithelium (Saghizadeh et al, 2001a; 2005).…”
Section: Molecular Alterations and Disease Markers Of Diabetes In mentioning
confidence: 99%
“…Expression of all considered ECM markers (collagen type I, collagen type III, and biglycan) is induced during ligament healing, with the exception of decorin that is reduced [18,40]. MMPs and TIMPs, critical indicators of tissue remodeling during healing, are upregulated in a wide range of healing tissue types [8,13,27,49]. MMPs-1, -2 and -9 along with TIMP-1 were of particular interest in this study due to their observed role in collagen breakdown in joint tissue [15,23,41].…”
Section: Introductionmentioning
confidence: 99%